Facile Preparation of MnO 2 Quantum Dots with Enhanced Fluorescence via Microenvironment Engineering with the Assistance of Some Reductive Biomolecules - Ma, Zhangyan; Sun, Yan; Xie, Jingwen; Li, Peipei; Lu, Qiujun; Liu, Meiling; Yin, Peng; Li, Haitao; Zhang, Youyu; Yao, Shouzhuo (ACS applied materials & interfaces, 2020)
MnO nanomaterials have aroused widespread attention because of their nanozyme activity, redox properties, good biocompatibility, and therapy-related activities. However, not many reports on self-luminescent MnO materials have been concerned to date, which greatly hampered their further development in various fields. In this paper, luminescent MnO quantum dots (MnO QDs) have been first prepared via a facile one-step ultrasonic method. With the assistance of bovine serum albumin (BSA) or cysteine (Cys), the synthesized MnO QDs (BSA-MnO QDs or Cys-MnO QDs) display strongly enhanced fluorescence (FL). The prepared BSA-MnO QDs with a particle size of about 1 to 2 nm show the maximum excitation and emission peaks at 320 and 410 nm with excellent salt stability, anti-photobleaching ability, and time stability. It is confirmed that BSA plays a dual function as the exfoliating agent to promote the exfoliation of bulk MnO nanosheets and as the capping agent to provide a friendly microenvironment for MnO QDs. Ag ions can destroy the microenvironment of BSA-MnO QDs owing to the in situ formation of Ag nanoparticles (Ag NPs) mediated by BSA on the surface of the QDs. Then, these Ag NPs can quench the FL intensity of the QDs by fluorescence resonance energy transfer. However, the FL strength of the BSA-MnO QDs is recovered after adding H O and NaHS since they may react with Ag NPs to produce Ag and Ag S, which further confirmed the role of BSA. This work not only opens up a facile and universal avenue to synthesize luminescent MnO QDs with enhanced FL but also provides a possible sensing platform through tuning the microenvironment of the MnO QDs. The MnO QDs with outstanding performance may show great potential as fluorescent probes in the fields of biological imaging, optical sensing, drug delivery, and therapy.